Privatization and local government reform in Germany: A slow train - Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The paper investigates the recent trends in privatization by local government organizations in Germany. It comes to the conclusion that the privatization policy has been two-directional: on the one hand, municipalities have reduced their economic activities, mainly by different forms of contracting out; on the other hand, they have expanded them into profitable fields. In many cases they have preferred a phantom privatization: government bodies have only been transferred into a private-law establishment. The paper examines the barriers to privatization and provides a strategy to overcome them.
Keywords: H4; 330; Kommunales Unternehmen; Privatisierung; Kommunalverwaltung; Verwaltungsreform; Deutschland